2011
DOI: 10.3892/or.2011.1353
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic-based analysis for identification of potential serum biomarkers in gallbladder cancer

Abstract: Abstract. Gallbladder cancer is the most common malignant tumor of the biliary tract. Early diagnosis of gallbladder cancer is difficult because of the latent onset and lack of good biomarkers. To identify new biomarkers that improve the early diagnosis and/or serve as possible therapeutic targets in gallbladder cancer is essential. In the present study, serum proteins were separated by two-dimensional gel electrophoresis (2-DE) in 3 patients with gallbladder cancer and 3 healthy volunteers. The differentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…We have also demonstrated the presence of S100A10 in cell culture supernatant (Figure 6), suggesting that S100A10 undergoes extracellular secretion. In addition, recently, S100A10 was detected in human serum and the list of plasma protein [49,50], thereby allowing blood level monitoring of S100A10 for further clinical validation as a biomarker for the L-OHP sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated the presence of S100A10 in cell culture supernatant (Figure 6), suggesting that S100A10 undergoes extracellular secretion. In addition, recently, S100A10 was detected in human serum and the list of plasma protein [49,50], thereby allowing blood level monitoring of S100A10 for further clinical validation as a biomarker for the L-OHP sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased levels of S100A10 are present in all anaplastic thyroid carcinomas, which is the most aggressive form of thyroid malignancy, suggesting that S100A10 plays a role in the progression of thyroid carcinomas [76]. Tan et al reported that high cytoplasmic S100A10 expression in advanced stage gallbladder carcinoma is associated with poor prognosis [77]. Overexpression of S100A10 is also associated with poor prognosis in lung carcinoma [78,79] and pancreatic cancer [80].…”
Section: S100a10 Expression In Cancersmentioning
confidence: 99%
“…A proteomic study by Wang et al, investigated the expression profiles of low and high metastatic cell lines identifying 24 proteins to be upregulated in highly metastatic cell lines including chloride intracellular channel 1, ezrin and vimentin [8]. Recently, S100A10 and haptoglobin were identified to be significantly upregulated in serum of gallbladder cancer and associated with poor prognosis [9]. …”
Section: Introductionmentioning
confidence: 99%